Cortrak feeding tube placement: interpretation agreement of the 'GI flexure' system versus X-ray. (25th June 2020) - Taylor, Stephen J; Manara, Alex; Brown, Jules; Allan, Kaylee; Clemente, Rowan; Toher, Deirdre
Abstract : Background: Blind (unguided) feeding tube placement results in 0.5% of patients suffering major complications mainly due to lung misplacement detected prior to feeding. Electromagnet-guided (Cortrak) tube placement could pre-empt such complications but undetected misplacements still occur due to incorrect trace interpretation. By identifying gastrointestinal (GI) flexures from the trace, 'the GI flexure system', it has been proposed that tube position can be interpreted. Aims: To audit agreement between standards of interpreting tube position: the Cortrak 'GI flexure' system versus X-ray. Methods: In 185 primary nasointestinal tube placements tube position determined by Cortrak trace interpretation (GI flexure) was retrospectively compared with radiological position in a blinded study. Findings: Radiological and Cortrak interpretation agreed in 92.2–98.3% of placements at different GI flexures. Discrepancy mainly occurred because some radiological images were unclear or did not cover all anatomical points. Conclusion: The GI flexure method of Cortrak interpretation appears safe but would necessitate prospective radiological investigation to definitively test equivalence.